Implementasi Asuhan Kebidanan Komunitas di Kelurahan Genuk Kecamatan Ungaran Kabupaten Semarang - Suci Rohandayani; Malisa; Oktafiana, Yusfani; Kurnia Dwi Pratiwi; Ratutriya; Putri Cahya; Restika Lelung; Listianingsih, Moneca Diah (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
A community is a collection of people who have at least one of the same characteristics such as geography, occupation, ethnicity, interests and others. Growth is a process of change characterized by an increase in physical size and body shape that can be assessed through measurements of height, weight, and head circumference. Development is a development that occurs in various aspects of a child. The aspects that develop include cognitive, motor, physical, language and speech, psychosexual and independence aspects. One of the contraction and creative ways to train children to regulate breathing patterns and physical activity can provide many benefits for growth and development. Yoga is an activity that does not give wrong or correct judgments but as a fun activity for children. The implementation method used in this community service is health counseling and demonstration about children's yoga to the target of toddlers and mothers of toddlers in Genuk Village RT.01/RW.03 Ungaran District, Semarang Regency. Implementation on May 31, 2024. The participants of this counseling activity were toddlers and mothers of toddlers totaling 15 people. The activity is carried out in stages (1) providing an explanation of the purpose of the activity; (2) distributing pre-tests to target mothers under five years old; (3) providing health counseling on "increasing maternal knowledge about children's yoga for optimal growth and development"; (4) conducting children's yoga demonstrations; (5) providing opportunities for the target to ask questions; (6) distributing post-tests to target mothers under five years. The activity showed that there was an increase in adolescent knowledge about adolescent healthy lifestyles, breastfeeding mothers regarding strengthening maternal nutrition during breastfeeding, toddler mothers about children's yoga for growth and development optimization after counseling on adolescent health and education, breastfeeding mothers and toddler mothers. Then conduct a children's yoga demonstration to optimize growth and development.  Conclusion: after this community activity was carried out, there was an increase in the community, especially adolescents, breastfeeding mothers and mothers under five about counseling on healthy lifestyle for adolescents, strengthening maternal nutrition during breastfeeding, and counseling on children's yoga as well as conducting children's yoga demonstrations.   Abstrak Komunitas adalah kumpulan orang yang memiliki karkteristik minimal satu karakteristik yang sama seperti geografis, pekerjaan, etnik, minat dan lain-lainnya. Pertumbuhan adalah proses perubahan yang ditandai dengan bertambahnya ukuran fisik dan bentuk tubuh yang dapat dinilai melalui pengukuran tinggi badan, berat badan, dan lingkar kepala. Perkembangan merupakan perkembangan yang terjadi pada berbagai aspek yang ada pada diri seorang anak. Aspek-aspek yang berkembang meliputi aspek kognitif, motorik, fisik, bahasa dan bicara, psikoseksual dan kemandirian anak. Salah satu cara kontraksi dan kreatif untuk melatih anak mengatur pola nafas dan aktivitas jasmani yang bisa memberikan banyak manfaat untuk pertumbuhan dan perkembangan. Yoga merupakan aktifitas yang tidak memberikan penilaian salah atau benar tapi sebagai suatu kegiatan yang menyenangkan untuk anak.  Metode pelaksanaan yang digunakan dalam pengabdian kepada masyarakat ini adalah penyuluhan kesehatan dan demonstrasi tentang yoga anak kepada sasaran balita da ibu balita di Kelurahan Genuk RT.01/RW.03 Kecamatan Ungaran, Kabupaten Semarang. Pelaksanaan pada 31 Mei 2024. Peserta kegiatan penyuluhan ini adalah balita dan ibu balita yang berjumlah 15 orang. Kegiatan dilakukan dengan tahapan (1) memberikan penjelasan tentang tujuan dilakukannya kegiatan; (2) membagikan pre-test kepada sasaran ibu balita; (3) memberikan penyuluhan kesehatan tentang “peningkatan pengetahuan ibu tentang yoga anak untuk optimalisasi pertumbuhan dan pekembangan”; (4) melakukan demonstrasi yoga anak; (5) memberikan kesempatan sasaran untuk bertanya; (6) membagikan post-test kepada sasaran ibu balita.  Kegiatan menunjukan ada peningkatan pengetahuan remaja mengenai pola hidup sehat remaja, ibu menyusui mengenai penguatan gizi ibu selama menyusui, ibu balita mengenai yoga anak untuk optmalisasi pertumbuhan dan perkembangan setelah dilakukan penyuluhan keseharan dan edukasi remaja, ibu menyusui dan ibu balita. Kemudian melakukan demontrasi yoga anak untuk optimalisasi pertumbuhan dan perkembangan. Setelah dilakukan kegiatan komunitas ini terdapat peningkatan masyarakat khususnya remaja, ibu menyusui dan ibu balita tentang penyuluhan pola hidup sehat remaja, penguatan gizi ibu selama menyusui, dan penyuluhan yoga anak serta melakukan demonstrasi yoga anak.